Making “academic talk” explicit: Research directions for fostering classroom discourse skills in children from nonmainstream cultures - Anne x Anne van Kleeck (Schweizerische Zeitschrift für Bildungswissenschaften, 2018)
This article focuses on making “school talk,” or classroom discourse, more explicit on two levels. One level involves making explicit for teachers both the nature of school talk, and the reasons why many children may come to school unfamiliar with the school talk register. Providing teachers with this awareness enables them, in turn, to make school talk explicit for their students by directly explaining the rules for engaging in this type of discourse to them. As tools for enhancing teacher awareness, this article clearly distinguishes the school talk and everyday social talk registers and provides information regarding the cultural variation in children learning to use school talk at home. The shortcomings of previous implicit approaches to teaching school talk are examined, and ways to make the rules for engaging in this register explicit for children are suggested.